2022
DOI: 10.14814/phy2.15375
|View full text |Cite
|
Sign up to set email alerts
|

Low‐carbohydrate diet score is associated with improved blood pressure and cardio‐metabolic risk factors among obese adults

Abstract: Obesity is associated with numerous co-morbidities and diet, is one of the modifiable risk factors for prevention against these obesity-related metabolic disorders.In the current study, we aimed to evaluate the association between adherence to low carbohydrate diet (LCD) score and serum lipids, glycemic markers, blood pressure, and anthropometric parameters among obese individuals. The current cross-sectional study is a combination of two projects with total participants of 359 obese individuals (body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…HFD alone has been shown to promote lipotoxicity in the kidney of mice [ 40 ], whereas ketogenic diet partially reverts diabetic nephropathy in db/db mice [ 41 ]. Taking in consideration the trend to decrease SBP observed in our study, we hypothesize that HFD could lead to cardiovascular protection [ 35 ], resulting in kidney protection. Additionally, the metabolic changes induced by HFD could also contribute to kidney protection.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…HFD alone has been shown to promote lipotoxicity in the kidney of mice [ 40 ], whereas ketogenic diet partially reverts diabetic nephropathy in db/db mice [ 41 ]. Taking in consideration the trend to decrease SBP observed in our study, we hypothesize that HFD could lead to cardiovascular protection [ 35 ], resulting in kidney protection. Additionally, the metabolic changes induced by HFD could also contribute to kidney protection.…”
Section: Discussionmentioning
confidence: 79%
“…These contradict some studies in the literature, demonstrating renal damage progression in HFD-fed mouse models [ 32 34 ]. However, a recent study performed by Pour Abassi et al 2022 showed that low-carbohydrate high fat diet can offer cardiovascular protection in obese adults [ 35 ], indicating that further studies are necessary to understand the mechanisms behind high fat diet regimen in CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant correlation between BMI the body fat. The higher the BMI, the higher the fat mass (Pour Abbasi, Shojaei, & Farhangi, 2022). This condition exacerbates health, for creating adjacent diseases, such as cardiovascular, type II diabetes and many others.…”
Section: Introductionmentioning
confidence: 99%
“…For example, aerobic exercise reduces blood vessel stiffness in the elderly (Wang et al, 2021). The effort to overcome BMI and high cholesterol due to obesity is to do a low-carbohydrate diet (Pour Abbasi et al, 2022) as well as do regular exercise. Exercise can protect adults from having metabolic syndrome (Menezes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%